Photo‐differential scanning calorimetry parameter study of photopolymers used in digital light synthesis. (25th December 2021) - Bachmann, Joel; Schmölzer, Stefan; Ruderer, Matthias A.; Fruhmann, Gabriele; Hinrichsen, Olaf
Abstract: Photopolymers for 3D printing belong to the largest material group used in additive manufacturing. One suitable characterization method is the photo‐differential scanning calorimetry (DSC) method, since UV light is used both as a probe in photo‐DSC measurements and for the curing process in digital light synthesis (DLS). The photo‐DSC method determines the speed and heat of the photopolymerization reaction, so it is an excellent method for characterizing the chemical process in DLS. In addition, the setup has been optimized in such a way that the photo‐DSC parameters used meet typical DLS process conditions. In particular, both the overlapping of the wavelengths of the light source and the photoinitiator and the similarity of the light intensities are very important. In this study, the commonly used dual curing, urethane methacrylate, DLS resin RPU 70 is thoroughly characterized. Several photo‐DSC experiments demonstrate the influence of wavelength, light intensity, temperature, relative humidity, and oxygen concentration in the atmosphere used on the curing process. Using the typical DLS parameters for light intensity and wavelength, the chemical reaction is mainly influenced by the oxygen concentration. The exposure time for vat photopolymerization processes decreases with decreasing oxygen concentration, which is why inert printing processes could have a positive effect on printing times. Additionally, it is shown that this method is also suitable for other DLS resins. Abstract :